Kelayakan Isi Lembar Kerja Siswa Bahasa Indonesia Sma Kelas X Semester 2 Kurikulum 2013 di SMA N 2 Sukoharjo - Kasih, Belinda Purwita, Prof. Dr. Markhamah, M.Hum (2017)
This study examines the feasibility of Contents Student Worksheet Indonesian High School Class X Semester 2 Curriculum 2013. This study aims 1) to describe the contents of LKS conformity with KI and KD on Curriculum 2013 2) describe the contents of LKS conformity with the approach (scientific) on the Curriculum 2013. This type of research to examine this issue is descriptive qualitative research because the purpose of this study describes the analysis of a text book, which this is done by describing the purpose of research which has been determined. The data collection technique used is the method of documentation. The analysis technique used is descriptive data processing techniques. The analysis technique used is descriptive data processing techniques. The results found that 1) there is an appropriate LKS Content and is not in accordance with the KI KD Curriculum 2013, 2) Fill LKS there is appropriate and is not in accordance with the Scientific Approach Curriculum 2013.